Dynamics of environmental consciousness and green purchase behaviour: an empirical study - Mishal, Aditi; Dubey, Rameshwar; Gupta, Omprakash K; Luo, Zongwei (International journal of climate change strategies and management, 2017)
Purpose The purpose of this paper is to investigate the relationships between environmental consciousness (ECO), green purchase attitude (GPA), green purchase intention (GPI), perceived customer effectiveness (PCE), green behaviour (GRB) and green purchase behaviour (GPB). Based on the statistical analyses, this paper offers some further research directions to advance the extant literature. Design/methodology/approach The theoretical model is firmly grounded in extant literature. To test the study hypotheses, the authors have developed a survey instrument following a two-stage process. The constructs were first operationalized by the authors and then pre-tested by experts. Dillman’s (2007) guidelines were then followed to gather data. Finally, the theoretical model was tested using multivariate statistical tools. Findings Results indicate that ECO has an influence on GPA and PCE; GPA has an influence on PCE and GRB; GPI has an influence on PCE; and GRB has an influence on GPB. Environmental benefit still ranks at the sixth position among eight product-selection criteria, as is evident from qualitative in-depth interviews indicating a primarily rationalistic and not an altruistic purchase approach. The gap in translation of ECO into GB and GPB can be attributed to costliness, non-availability with less variety, lack of brand reputation of green products and budget constraints for customers. Research limitations/implications The study faces the limitation of generalizability of the results because it was carried out in a particular state in India; it may not be the perception of the country as a whole. The bias owing to social desirability, selective memory and telescoping with the use of self-reported data could also be a limitation for the current empirical study. Originality/value This study aimed to extend pro-environmental behaviour studies beyond developed countries and to empirically validate the models built on the theory of ECO leading to GPB, especially for India, a rising market. A novel approach to empirically discuss the situational and market factors will provide a much-needed thrust for research on these lines.